Protective effects of safranal on diabetic retinopathy in human microvascular endothelial cells and related pathways analyzed with transcriptome sequencing - Xiao, Qin; Sun, Yao-Yao; Lu, Zhan-Jun; Li, Shan-shan; Su, Riguga; Chen, Wen-Lin; Ran, Lin-Lin; Zhang, Surina; Deng, Kaixin; Yu, Wen-Zhen; Chen, Wenqian (Frontiers in Endocrinology, 2022)
Aim: To determine the effect of safranal on diabetic retinopathy in vitro and its possible mechanisms. Methods: We used human retinal microvascular endothelial cells (HRMECs) to test the influence of safranal in vitro. High glucose damage was established and an safranal was tested at various concentrations for its potential to reduce cell viability using the MTT assay. We also employed apoptosis detection, cell cycle detection, a transwell test, and a tube formation assay to look into safranal's inhibitory effects on high glucose damage at various doses.. Furthermore, mRNA transcriptome sequencing was performed. mRNA expression levels in a high glucose damage model, a high glucose damage model treated with safranal, and a blank control were compared to find the possible signaling pathway. Western blotting was used to confirm the expressions of several molecules and the levels of phosphorylation in each for the newly discovered pathway.Results: Cell proliferation was inhibited under a high glucose condition but could be protected by safranal at different concentrations (P<0.001). Flow cytometry results suggested safranal also protected cells from apoptosis (P=0.006). A transwell test demonstrated reduced invasiveness of safranal-treated cells in a high glucose condition (P<0.001). In a tube formation investigation, there were noticeably more new branches in the high gloucose group compared to a high glucose treated with safranal group (P<0.001). In mRNA expression patterns on transcriptome sequencing, the MAPK signaling pathway showed an expression ratio. With western blotting, the phosphorylation level of p38-AKT was elevated under a high glucose condition but could be inhibited by safranal. The expression of molecules associated with cell adhesion, including E-cadherin, N-cadherin, Snail, Twist, and fibronectin also changed significantly after safranal treatment under a high glucose condition. Conclusion: Safranal can protect diabetic retinopathy in vitro, and the p38-AKT signaling pathway was found to be involved in the pathogenesis of diabetic retinopathy and could be inhibited by safranal. This pathway may play a role by influencing cell migration and adhesion.